Peran Guru Pesantren dalam Tranformasi Etika Santri Melalui Pembelajaran Kitab Ta'lim Muta’allim di Pondok Pesantren Raudlatul Muttaqin Talun Sidogembul Sukodadi Lamongan (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Teachers at Islamic boarding schools (pondok pesantren) not only serve as educators but also as role models and mentors in the application of values taught in the book Ta'lim Muta'allim. They function as role models, providing a living example of the implementation of Islamic manners and ethics. The term